A review of sources, multimedia distribution and health risks of perfluoroalkyl acids (PFAAs) in China. (June 2015) - Wang, Tieyu; Wang, Pei; Meng, Jing; Liu, Shijie; Lu, Yonglong; Khim, Jong Seong; Giesy, John P.
Highlights: PFOS and PFOA are the predominant compounds found among environmental media. PFAAs emissions from industrial source are significant higher than domestic source. Higher levels of PFAAs were detected in more industrialized and urbanized areas. Regional urbanization is closely related to emission and contamination of PFAAs. Risk assessment of PFAAs in China has lagged behind those in developed countries. Abstract: Perfluoroalkyl acids (PFAAs) have been recognized as emerging pollutants because of their ubiquitous occurrence in the environment, biota and humans. In order to investigate their sources, fate and environmental effects, a great number of surveys have been carried out over the past several years. In the present review, we summarized the status of sources and emission, concentration, distribution and risks of PFAAs in China. Concentrations of PFAAs, especially perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in various environmental media including water, sediment, soil, rain, snow and organisms, as well as human tissues are summarized based on the available data. Concentrations of PFAAs in aquatic systems are higher in relatively more industrialized and urbanized areas than those from the less populated and remote regions in China, indicating that their emission and distribution are closely related to regional urbanization and industrialization. PFAAs and related products have been widely used over the past several decades, which have brought about high concentrations detected in environmental matrixes, biota and even local residents. Ecological risk assessment of PFAAs is still less developed in China. Most existing studies compared concentrations of PFAAs to guideline values derived for single species to evaluate the risk. In order to reveal the transport, partitioning and degradation of PFAAs in the environment, further studies on their behavior, fate, bioaccumulation and adverse effects in different trophic levels should be conducted.